Longhouse Spatial Elements for Sustainable and Affordable Housing Construction - Janet Victoria Anak Stia; Siti Hamidah Abdul Hamid; Siti Akhtar Mahayuddin; Mohd Dzuliqyan Jasni; Mohd Zul Aswad Zulkifli (Advances in Humanities and Contemporary Studies, 2023)
Traditional longhouse of the Dayak people in Sarawak was considered as a village under one massive roof. Some longhouses can have around twenty to thirty families living under one roof. Despite the concept of living together under one roof, the different families have their own private apartment. Longhouses basically have four spatial elements namely the open veranda, long gallery, apartment, and loft. Open veranda and long gallery are shared among the different families while apartment and loft are private spaces for them. In response to the Malaysian Government’s effort in the Twelve National Plan (2021-2025) for every Malaysian to have equivalent right to affordable housing with sustainable approaches, the idea of integrating traditional longhouse spatial elements in sustainable and affordable housing development seems indispensable. Study had been conducted to fifteen Dayak longhouses around Sarawak. Collection of data had been done by inspection on the existence of the longhouse spatial elements and data were collected in Inspection Checklists and Record Card. The outcome from the study found four types of spatial elements arrangements in existing traditional longhouse with the presence and absence of the four main spatial elements. From the outcome can be used as an idea for sustainable and affordable housing. Rather than constructing stratified dwellings, implementing traditional longhouse as a model could be another cost saving option. The application of this type of housing is expected to enhance the quality of life and capable of meeting the needs of local population.